2002
DOI: 10.1046/j.1523-5378.2002.00097.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Gastric Ulcer and Helicobacter pylori VacA Detected in Gastric Juice Using Bead‐ELISA Method

Abstract: VacA in gastric juice could be directly detected by bead-ELISA. In this study, the diversity of disease outcome was associated with not the quality but the quantity of VacA. Therefore, not only the quality but also the quantity of VacA is important etiological factors in the pathogenesis of mucosal damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…It has also been reported that s1 type vacA gene products are secreted at higher levels than s2 type vacA products (Sewald et al 2008a). Other studies, which examined the relationship between the quantity of VacA and gastric ulcers using a very sensitive method, bead-ELISA, revealed that the amount of VacA secreted by H. pylori correlates with the presence of gastric ulcers (Shirasaka et al 2002). Again, H. pylori strains that possess a type s1/m1 vacA allele are associated with an increased risk of gastric cancer and enhanced gastric epithelial cell injury (Atherton et al 1997;Peek and Crabtree 2006) compared with vacA s2/m2 strains.…”
Section: Structure and Function Of Vacamentioning
confidence: 99%
“…It has also been reported that s1 type vacA gene products are secreted at higher levels than s2 type vacA products (Sewald et al 2008a). Other studies, which examined the relationship between the quantity of VacA and gastric ulcers using a very sensitive method, bead-ELISA, revealed that the amount of VacA secreted by H. pylori correlates with the presence of gastric ulcers (Shirasaka et al 2002). Again, H. pylori strains that possess a type s1/m1 vacA allele are associated with an increased risk of gastric cancer and enhanced gastric epithelial cell injury (Atherton et al 1997;Peek and Crabtree 2006) compared with vacA s2/m2 strains.…”
Section: Structure and Function Of Vacamentioning
confidence: 99%
“…A recent in vivo study by Shirasaka et al detected only 20 -800 pg/ml VacA in gastric juice of 48 H. pyloripositive patients using a bead-ELISA [19]. In view of these data, the physiologic relevance of the results from in vitro studies seems to be rather limited.…”
Section: Studies In Animals Have Revealed That T-cell Responses Towardsmentioning
confidence: 99%
“…, in contrast, reported in a technically challenging and well-done study that recombinant VacA inhibited translocation of NFAT in Jurkat T cells and also prevented upregulation of CD69 in these cells after stimulation of the T-cell receptor [11]. However, VacA concentrations have been used (40 µ g/ml) which do not occur in vivo at the site of H. pylori infection in the stomach (see above) [19]. In particular, lymphocytes located predominantly under the subepithelial barrier will not be exposed to such high concentrations of a single protein.…”
mentioning
confidence: 99%
“…Based on the capacity of VacA to induce ulceration in mice when administered intragastrically, it has been suggested that VacA contributes to the pathogenesis of gastric ulceration in humans. The intragastric concentration of VacA in animals receiving intragastrically administered VacA substantially exceeds the 20–800 pg per mL concentration of VacA estimated to be present in gastric juice, based on a bead-based ELISA performed on samples from H. pylori -positive patients [ 165 ], but local concentrations of VacA at sites of H. pylori interaction with gastric epithelial cells might be considerably higher than concentrations in gastric juice. In studies of gerbils experimentally infected with H. pylori , vacA mutant strains are less likely than isogenic wild-type strains to produce gastric ulcers [ 161 ].…”
Section: Activity Of Vaca In Animal Modelsmentioning
confidence: 99%